Análisis del origen y evolución del impuesto al activo - López González, Moisés (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The present work incorporates a target analysis that, in México, motivated the sprouting of the Tax to the Assets, its evolution, the awaited and obtained collection from its creation in 1988 and to the fiscal year of 2007, with the intention of giving a conclusion referring to the fulfillment of the original objectives of this Tax. In order to make this study, 23 initiatives of law were analyzed, between which it emphasizes the initiative of law presented at the Congress of the Union on December 15, 1988, and that gave rise to then the new Law of the Tax to the Assets of the Companies, published in the official Newspaper of the Federation on December 31, 1988, and with use from 1º. Of January of 1989, in where the basic characteristics and the reasons are exposed that justify this Law, the mechanics of original calculation of the Tax to the Assets, also were analyzed the reasons that were exposed in the initiatives of law through, which the reforms happened to this tax were promoted, until arriving at its present calculation, the shaped data of collection in the laws of income of the Federation and in Accounts of the Federal Public Property of the corresponding exercises from 1989, to 2007 and 2005, respectively. The result of this study concludes to the Collection like fundamental axis of the other reasons, same that they aim at the Social Development. The awaited collection was fulfilled by the exercises: from 1989 to 1994, from 1996 to 1998, from 2000 to 2001 and from 2006 to 2007 not yet there are data. By the years of 1995, 1999, while in the exercises 2002 and 2005 the awaited collection was not fulfilled reason, why it affirms that the objectives raised by the legislators in the initiatives of creation and reform to the Tax to the Assets were not obtained.

El presente trabajo incorpora un análisis de los objetivos que, en México, motivaron el surgimiento del Impuesto al Activo, su evolución, la recaudación esperada y obtenida desde su creación en 1988 y hasta el ejercicio fiscal de 2007, con el objeto de dar una conclusión referente al cumplimiento de los objetivos originales de dicho Impuesto. Para realizar este estudio se analizaron 25 iniciativas de ley, entre las que destaca la iniciativa de ley presentada ante el Congreso de la Unión el jueves 15 de diciembre de 1988, y que dio lugar a la entonces nueva Ley del Impuesto al Activo de las Empresas publicada en el Diario oficial de la Federación del 31 de diciembre de 1988, con vigencia a partir del 1º. de enero de 1989, en donde se exponen las características principales y las razones que justifican dicha Ley, la mecánica de cálculo original del Impuesto al Activo, asimismo se analizaron los motivos que se expusieron en las iniciativas de ley a través de las cuales se promovieron las reformas ocurridas a dicho impuesto, hasta llegar a su cálculo actual, los datos de recaudación plasmados en las leyes de ingresos de la Federación y en las Cuentas de la Hacienda Pública Federal de los ejercicios correspondientes de 1989, hasta 2007 y 2005, respectivamente. El resultado de este estudio concluye a la Recaudación como eje fundamental de los demás motivos, mismos que apuntan al Desarrollo Social. La recaudación esperada se cumplió por los ejercicios: de 1989 a 1994, de 1996 a 1998, de 2000 a 2001, mientras que por los ejercicios de 2006 y 2007 aún no hay datos. Por los años de 1995, 1999 y de 2002 a 2005 no se cumplió la recaudación esperada por lo que se afirma que, por esos ejercicios, no se lograron los objetivos planteados por los legisladores en las iniciativas de creación y reforma al Impuesto al Activo.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2007-0071; Recaudación; SHCP; Fiscal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5861